(untitled) (Marketing Journal, 2025)
This article examines the application of artificial intelligence (AI) technologies to optimize production processes in industrial enterprises. The study utilizes theoretical analysis, a comparative study of international practices, and methods for evaluati ng the effectiveness of AI tools such as machine learning, deep learning, computer vision, and natural language processing. The results demonstrate that the proper application of AI technologies enables industrial enterprises to improve production efficien cy, predict failures, improve quality control, and reduce costs. Using international experience as examples, the article analyzes the application of AI by leading industrial enterprises in Germany, the United States, China, and South Korea, identifying the ir advantages. It is argued that the primary focus of AI development in industrial enterprises should be on ensuring data quality, training specialists, and a phased implementation strategy.